Studi perbandingan rencana strategi pada bank daerah syariah - Radliyah, Diana Rahmah; Kumala, Alfaina Dica Putri; Sadiyah, Nailatus (Maliki Interdisciplinary Journal, 2023)
The purpose of this research is to inform the wider community about the comparison of strategic plans at thre local Islamic banks namely Bank Jateng Syariah, BJB Syariah and Bank NTB Syariah. This research uses a research method in the form of a literature review. Where the objects used are Bank Jateng Syariah, BJB Syariah and Bank NTB Syariah, while the data or information used is a type of secondary data. The data obtained is obtained from the 2022 annual report on Bank Jateng Syariah, BJB Syariah and Bank NTB Syariah.The results of the three Islamic bank strategic plans are Bank Jateng Syariah concentrates on product marketing, funding, and collection, strengthening human resources, and providing Islamic banking products and services with superior service levels. Bank BJB Syariah concentrates on distributing financing, raising retail funds, developing Planning Savings products, and improving activities and work culture that focus on business growth. Bank NTB Syariah's short-term and medium-term plans include consolidating commercial banks, increasing capital, improving business performance, developing products and services, developing IT systems and infrastructure, and increasing business synergies and strategic alliances